THEORETICAL BASIS OF CREATIVE THINKING DEVELOPMENT IN FOREIGN LANGUAGE EDUCATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the theoretical frameworks and pedagogical strategies essential for developing creative thinking in foreign language education. In the contemporary globalized world, language learning is no longer merely about grammatical competence but involves the ability to synthesize information, solve problems, and express original ideas. The study examines various psychological and cognitive theories—such as Divergent Thinking and Bloom’s Taxonomy—and analyzes how they can be integrated into the EFL classroom. Through a systematic literature review and empirical data analysis, the paper demonstrates the correlation between creative task implementation and increased linguistic proficiency. The results suggest that fostering a "creative environment" significantly enhances student engagement and long-term retention of language structures.